Phosphorus-Use Efficiency Modified by Complementary Effects of P Supply Intensity With Limited Root Growth Space - Gong, Haiqing; Kabeto Wako, Bilisuma; Xiang, Yue; Jiao, Xiaoqiang (Frontiers in Plant Science, 2021)
Space availability and the maintenance of adequate phosphorus (P) supply in the root-zone are essential for achieving high yield and P-use efficiency in maize production by manipulating root morphology and arbuscular mycorrhizal (AM) fungi colonization. A major trade-off exists between root growth and AM colonization, which is influenced by soil P supply intensity and space availability. However, how soil P manipulates root morphological characteristics and AM colonization to compensate for the limitation of root-growth space induced by high-planting density is not clear. Therefore, pot experiments were conducted to investigate interactions between root growth and AM fungi by optimizing soil P supply to compensate for limited root growth space induced by high-planting density. Similar shoot biomass and P uptake values were obtained in P200 (200 mg P kg-1 soil) under D=40 (i.e., diameter of pot is 40 cm) and P400 under D=30, and similar values were obtained for root length, tap root length, root angle, lateral root density, and AM colonization. However, improvement in P supply in the root-zone, shoot biomass, and P uptake in P400 under D=20 were lower than in P200 under D=30, and there were no significant difference in root parameters between P200 and P400 under D=20; similarly, root growth and AM colonization exhibited similar trends. These results suggest that optimizing P supply in the root-zone to regulate the interaction between root morphological traits and AM colonization can compensate for limited root-growth space. Although P supply in the root-zone increased after the root-growth space was compressed, it could not meet the P demand of maize; thus, in order to achieve the most efficient use of P under intensive high-density maize production, it is necessary to optimally coordinate root growth space and P supply in the root-zone.